Hong Kong and the Asylum-Seekers from Vietnam - Davis, Leonard. author. aut Link
XII, 255 p.
Keywords: Leonard Davis gives the background to the 15-year-long saga of Hong Kong and the asylum seekers from Vietnam. In the run-up to 1997 there has been increasing tension associated with the presence of 50,000 Vietnamese men, women and children in Hong Kong. The principal themes of the book cover screening and repatriation, the violence in the detention centres, the plight of children and the urgent need for the international community to be more generous to the refugees.